Intestinal Spirochetes in Cancer Patients: Our Experience and Review of the Literature. Issue 3 (May 2020) - Cheema, Asima; Jejelowo, Oluwafisayo; Syed, Misbahuddin; Ramsakal, Asha; Greene, John N.
Abstract : Abstract: The clinical significance of human intestinal spirochetosis is a debated topic, with possible links to various gastrointestinal symptoms such as diarrhea and hematochezia. The most commonly associated organisms in humans involve Brachyspira aalborgi and Brachyspira pilosicoli . However, the presence of spirochetes within the colorectal epithelium does not always suggest pathogenicity, and treatment does not always lead to symptom improvement. Men who have sex with men and patients infected with the HIV have been considered at higher risk of colonization and subsequently becoming symptomatic, possibly related to an underlying immunosuppressed state. We present a series of 3 case reports of human intestinal spirochetosis in immunocompromised cancer patients at the Moffitt Cancer Center and Research Institute. The aim of this study is to increase awareness of this entity in immunocompromised cancer patients and non–HIV-positive immunosuppressed patients, particularly when presenting with gastrointestinal symptoms of unclear etiology. Abstract : Human intestinal spirochetosis (HIS), associated in humans with Brachyspira aalborgi and Brachyspira pilosicoli, has typically been associated in those infected with the human immunodefi ciency virus. However, the aim of this study is to describe immunodefi cient cancer patients identifi ed with HIS and discuss the debatable effect of treatment with clinical resolution of gastrointestinal symptoms.